Danantara Establishment’s Political Economy and Investor Confidence - Rullya Andriani (Jurnal Cakrawala Hukum, 2026)
This study examines the implications of the establishment of the Danantara Investment Management Agency on investor confidence in Indonesia. The formation of Danantara as a state investment institution raises concerns related to legal-political dynamics, institutional governance, and oversight mechanisms in the management of state assets. The purpose of this study is to analyze how these factors influence investor confidence in the national investment climate. This study employs a socio-legal research approach using conceptual, statutory, and ethnographic methods to assess the relationship between legal frameworks, governance practices, and social realities. The findings indicate that Danantara is designed as a fiscal policy instrument to optimize the management of state-owned enterprise assets and support national economic growth. However, several governance issues persist, particularly concerning the clarity of oversight mechanisms, institutional independence, and the transparency and accountability of financial reporting. These conditions may affect investor risk perception and trust. Therefore, the effectiveness of Danantara depends on the implementation of good governance, transparency, and independent oversight to enhance investor confidence and ensure sustainable investment.